WPIS DO REJESTRU DZIAŁALNOŚCI REGULOWANEJ - Strzelbicki, Michał (Wydział Prawa i Administracji UAM, 2005)
The Act on Freedom of Economic Activity passed by the Parliament of the Republic of Poland on 2 July 2004 introduced obligatory registration of one’s business activity, which is a new form of influence that organs of public administration may exercise in respect of businesses set up and run in Poland. A thorough and detailed view of the regulated business activity treated as a legal institution is presented and various aspects of the Act, starting from the characteristics of the issues relating to the statutory definition of regulated business activity, through issues like the reasons of behind the establishing of a register of business activity, the legal regulations, types of business activity, legal nature of the entry, grounds for refusal to make an entry and consequences of a failure to make an entry, as well as supervision of the entrepreneur whose business activity has been entered in the register and the type of decisions prohibiting business activity, are discussed. Concluding, the author attempts to assess whether the decision to abandon the existing permits and licences to carry out business activity and introduce an obligation to enter one’s specific business in the regulated activity register is justified.
ENTRY INTO THE REGULATED ACTIVITY REGISTER